2018
DOI: 10.25165/j.ijabe.20181103.3846
|View full text |Cite
|
Sign up to set email alerts
|

Assessing effects of deficit irrigation techniques on water productivity of tomato for subsurface drip irrigation system

Abstract: Water resources are subjected to ever-increasing supply constraints due to extensive agricultural water demand for irrigated lands. Therefore, water-saving irrigation strategies need to be explored. The present study was conducted to explore the possibilities of using regulated deficit irrigation (RDI) and partial root zone drying irrigation (PRD) methods as water-saving irrigation techniques for subsurface irrigation. The objective of this study are to assess the effects of RDI and PRD irrigation on the water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Notwithstanding the bad quality of the water (high pH, high EC) potatoes grow well and looked healthy ( Figure 26). The success of substituting pivot irrigation by subsurface fertigation in increasing water use efficiency and yields has already been reported in literature by several authors (Al-Ghobari et al, 2018, Hashem et al, 2018, O'Neill et al, 2008, Valentin et al, 2020 and also holds for the arid El Oued region. So, introduction of a subsurface system does have potential for increasing sustainability of potato growth.…”
Section: Discussionmentioning
confidence: 66%
“…Notwithstanding the bad quality of the water (high pH, high EC) potatoes grow well and looked healthy ( Figure 26). The success of substituting pivot irrigation by subsurface fertigation in increasing water use efficiency and yields has already been reported in literature by several authors (Al-Ghobari et al, 2018, Hashem et al, 2018, O'Neill et al, 2008, Valentin et al, 2020 and also holds for the arid El Oued region. So, introduction of a subsurface system does have potential for increasing sustainability of potato growth.…”
Section: Discussionmentioning
confidence: 66%
“…Irrigated agricultural land is the primary user of water resources, representing roughly 70% of total water withdrawal [1]. However, the worldwide irrigated land area must be increased by more than 20%, and the total irrigated crop yield must be increased by 40% by 2025 to ensure food security for 8 billion people [2].…”
Section: Introductionmentioning
confidence: 99%
“…Provide water as drop after drop on the surface soil to the plant during growing based on plant age in a low-pressure drip irrigation system which decreases costs and water irrigation and got high quality of crop (Tiwari et al, 1998). Hashem et al, (2018) showed that there is minimum water applied which plants need and water stress by using drip irrigation which led to low water losses and percolation deeply. The high yield of lettuce and cabbage crop was of 150% ETc.…”
Section: Introductionmentioning
confidence: 99%